Reproductive Toxicity Of Non-Steroidal Anti-Inflammatory Drugs - Fia Fia (Ebers Papyrus, 2014)
Non-steroidal anti-inflammatory drugs (NSAIDs) are the one of a drug-class that is generally consumed by most of pregnant women in the world for many different indications during their pregnancy. It is important for doctor who prescribes to know well the safety of these drugs, since these drugs are also given for indications (of illnesses) that also could give detrimental effects in pregnancy, as viral infections. Here in this article, the effects of NSAIDs drugs, especially diclofenac is assessed. This review is based on journals in studies that had been conducted to know the reproductive toxicity of NSAIDs. It is known now that NSAIDs in preconception time could affect women's fertility and in first trimester possibly could increase the risk of spontaneous abortion. In the second trimester they are associated with kidney disorder of the offspring and in the last trimester they cause premature closure of ductus arteriosus and leading to pulmonary hypertension in the newborn infants. So it is advised that the use of these drugs for pregnant women should be given only for certain indications when there are no other option for a saver drug.